2015
DOI: 10.2340/16501977-1949
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of gait training using a treadmill with and without visual biofeedback in patients after stroke: A randomized study

Abstract: Gait training using a treadmill resulted in improvements in the gait and functional capacity of patients. The use of biofeedback gives better results in improving gait cycle length, duration of gait phases and swing phase speed compared with exercise on a treadmill alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
63
0
3

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 35 publications
1
63
0
3
Order By: Relevance
“…Additionally, knowledge of performance provided by the AGRF-guided biofeedback may enhance the patient’s engagement during training, and increase the efficacy of rehabilitation. Similar to previous investigations employing biofeedback as a post-stroke gait training tool for targeting spatio-temporal parameters such as step length and stance time [14, 15], we believe that AGRF-based feedback may be a valuable gait training strategy worthy of investigation. Reduced AGRF has been demonstrated to be an important biomechanical impairment in people post-stroke, and has been associated with over ground gait speed, gait asymmetry, and stroke severity [1, 2, 12, 35].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Additionally, knowledge of performance provided by the AGRF-guided biofeedback may enhance the patient’s engagement during training, and increase the efficacy of rehabilitation. Similar to previous investigations employing biofeedback as a post-stroke gait training tool for targeting spatio-temporal parameters such as step length and stance time [14, 15], we believe that AGRF-based feedback may be a valuable gait training strategy worthy of investigation. Reduced AGRF has been demonstrated to be an important biomechanical impairment in people post-stroke, and has been associated with over ground gait speed, gait asymmetry, and stroke severity [1, 2, 12, 35].…”
Section: Discussionsupporting
confidence: 76%
“…Although there is a paucity of systematic investigations on the use of real-time biofeedback during post-stroke gait training, biofeedback during gait has been shown to be effective at modulating step asymmetry in post-stroke individuals [14, 15], trunk lean in able-bodied individuals [16], and knee adduction moment in individuals with varus knee alignment [17]. Force platform biofeedback during gait has been studied for improving limb loading symmetry following total hip arthroplasty [18] and gait asymmetry in trans-tibial amputees [19].…”
Section: Introductionmentioning
confidence: 99%
“…Os achados do presente estudo corroboram com os achados de outros autores que tem estudado as repercussões de atividades terapêuticas para a melhora na funcionalidade de sujeitos pós AVE 27,28,29 , relatando melhoras após diferentes protocolos de intervenção, como o uso da dança, treino em esteira e mesmo a terapia convencional.…”
Section: Discussionunclassified
“…By using a force treadmill to quantitatively analyze gait patterns and detect gait abnormalities, medical therapists can adjust the intensity of treadmill training on an individual basis. In addition, previous studies have shown that the feedback of auditory, vibrotactile, and visual gait information can alter or improve gait features such as walking speed [30, 31], gait coordination [32], trunk sway [33], stride length [31], hip mechanics [34], cadence [31], step length symmetry [35], knee movement [36], gait cycle length [37], duration of gait [37], and swing phase speed [37]. With the capability of generating many important gait features, force treadmills represent an ideal platform for implementing such biofeedback systems.…”
Section: Introductionmentioning
confidence: 99%